Use of Bladder diary as diagnostic and therapeutic tool for Overactive Bladder - Mohsin, Raheela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate use of diary for teaching patient with overactive bladder and see its therapeutic effects in terms of reduction in their symptoms Methods: A single-blind randomized clinical trial, regarding “Effects of Bladder Training and behavioral intervention in Female Patients with Over active Bladder syndrome, attending Urogynecology clinic at The Aga Khan University Hospital Karachi, Pakistan: A Randomized Controlled Trial (OAB) trial” We here present the additional conclusions drawn from results of ARM-1.Arm-1 patients were managed by behavioral intervention only and were asked to fill 7 days diary in 12 weeks .By using WHO software a minimum of 114 women needed to meet the study objectives. We recruited 50 women in each group (150 totals) as there was a possibility of drop out.We calculated the mean difference in fluid intake and reduction in urinary frequency, urgency, nocturia before and after educating the patient using the paired-T Test. Results: A total of 47 women completed follow up visits for overactive bladder treatment ARM-A. (Mean ± SD) Mean fluid intake on first diary was 2392.9 ml while on last diary fluid intake was reduced to 177.1ml with mean fluid intake difference of 621.8ml+622.2(p<0.00).The mean reduction in frequency of micturition during day and nocturia was 2.9+2.7(P<0.00) and 0.59+ 0.99(p<0.00) respectively. The mean decrease in urgency score and reduction in leak accident was 1.19+1.2(p<0.00) and 0.9+0.95(p<0.00) respectively. Conclusions: The bladder diary for women with OAB has both diagnostic and therapeutic effect. In developing countries it is an easy least expensive but time consuming method of treatment for simple cases of OAB.